Multiple sclerosis: association with the interleukin-1 gene family polymorphisms in the Turkish population - ARMAN, AHMET; ÇOKER GÜRKAN, AJDA (TAYLOR & FRANCIS LTD, 2013)
Background: Multiple Sclerosis (MS) is a neurodegenerative disease. It involves inflammation and demyelination. Since cytokines play an important role in the development of MS, genes encoding cytokines such as the Interleukin (IL)-1 family are candidate genes for MS susceptibility. Objective: To determine the relationship between IL-1 gene family and MS in the Turkish population. Methods: A total of 409 MS patients and 256 healthy controls were included in the study. IL-1A -889 (rs1800587), IL-1 RN variable number tandom repeat (VNTR), IL-1B -511 (rs 16944) and IL-1B +3953 (rs 1143634) polymorphisms were investigated from the genomic DNA, obtained via blood samples. Results: No association was found between IL-1A and IL-1RN polymorphisms and susceptibility to MS. However, we have found significantly decreased frequency of IL-1B -511 genotype (p = 0.004) in MS patients compared to controls. In addition, there was a significant association between IL-1B -511 (1/2) genotype and early onset MS (EOMS) (p = 0.0001). Conclusions: Individuals with the 2/2 genotype of IL-1B -511 have significantly decreased incidence of MS, suggesting a protective role for this genotype in the Turkish population. Additionally, IL-1B -511(1/2) genotype was determined as a possible risk factor for EOMS.
Keywords: demyelinating disease; interleukin-1; cytokine; genotype distribution; RECEPTOR ANTAGONIST IL-1RA; DISEASE SEVERITY; RHEUMATOID-ARTHRITIS; ADHESION MOLECULE; IL-1-BETA; SUSCEPTIBILITY; CELLS; RISK; RELEVANCE; INTRON-2